Investing Efficiently in Education and Active Labour Market Policies in Slovakia - Klein, Caroline (OECD Economics Department Working Papers, 2013)
In Slovakia, educational outcomes are below the OECD average and are too dependent on the socioeconomic background of students. Unemployment is high and the school-to-job transition process does not work well. Spending on education and active labour market policies are very low by international standards. While reforms are under way in both areas, further efforts are needed to support the domestic drivers of growth. At a time of fiscal consolidation, these two policy areas should at the least be protected from budgetary cuts while every opportunity for efficiency gains should be seized. Not least because of the high level of long-term unemployment, more emphasis should be placed on activation policies, particularly on placement services, which are currently underfinanced but also insufficiently evaluated. Educational achievements and thus future labour market outcomes could be improved by re-allocating resources to teaching activities, in particular for disadvantaged pupils. Developing work-based vocational education would also facilitate the transition from school to work. This Working Paper relates to the 2012 OECD Economic Survey of the Slovak Republic (www.oecd.org/eco/surveys/slovakia2012)